Suplementary Reading Materials Based on Tourism Spot for Junior High School Students in Southwestern Maluku - Fredi Meyer; Febryanto Umpenawany; Juwaher Makatita (Jurnal Bintang Pendidikan Indonesia, 2023)
The objective of the study was to find out how supplementary Reading Materials Based on Tourism Place For Junior High School Students in Southwestern Maluku. The Literature study was carried out Lack of students’ understanding affect their activities for reading materials in classroom activity. Based on the researcher did observation at Junior High School Students, as result, the problem to the students’ in learning reading material. Lack of reading Materials made their students lowest in reading. When the teacher supplementary reading Materials Based on Tourism Place. The result of reading material has developed into three units which enable the students consisting of new vocabulary, and exercises. Meanwhile the result reading Materials Based on Tourism Place got positive input for students.